Contribution of Highland Bamboo for Income of the Households and Challenges in Gurage zone, Central Ethiopia - Hailu, Hiwot; Girma, Gonche; Ababu, Tesfanesh; Abate, Tensaye; Abebe, Mister (International Journal of Business, Economics, and Social Development, 2025)
Bamboo resource has numerous socioeconomic, ecological and cultural benefits. In Ethiopia, local farmers rely on bamboo as an alternative livelihood option. It provides a considerable share for the various household incomes. The main purpose of this study was to assess challenges and the contribution of bamboo for income of the households in Gurage Zone, across central Ethiopia. A sample of 216 households, were selected by using multistage sampling procedure. Data was collected through household survey, focus group discussion and review of reports. Descriptive, frequency and multiple linear regression model methods were used to estimate the contribution of bamboo and to identify determinants bamboo production. The finding revealed that respondents were highly relying on bamboo for household use, construction, fuel wood, fencing and fodder for livestock. The result of bamboo income share shows that, 14% Bamboo can contribute to the total income of the households. Income from bamboo ranks third next to crop and livestock production. The result of multiple linear regression model revealed that, Educational level of household head and Distance to the market were negatively affect income generated from bamboo. In contrast, the culm price Bamboo was positively and significantly affect income generated from bamboo production. Market related and knowledge on bamboo production and processing were the most challenges identified by the households. Bamboo contributes a remarkable income share for households in the study area. Creating conducive production environment for the bamboo sector plays a vital role to improve the income and livelihood of farmers.